Modeling of fault detection and isolation in pitch control of wind energy conversion systems via digital twins - Branco , César Tadeu Nasser Medeiros; Silva , Jonny Carlos (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
There is a growing trend in renewable energies for wind harvesting and power generation. As new offers for the energy sector continue to rise up, the operation and maintenance team plays a vital role in increasing the availability and decreasing downtime of wind turbines subassemblies, based on conditional monitoring of their assets. This paper developed an approach for fault detection and isolation of the pitch control system on a direct drive permanent magnet synchronous generator using dynamic modeling and digital twins. The work presents two models of wind turbines, whose conditions were replicated in a multi-domain simulation software and the analyses were conducted under rotor constant speed. One concept represents a wind turbine model with a fault in pitch system, while the other is a healthy replica or a virtual model. Through the difference between three observable variables, namely: active power, angular speed and pitch angle, it was possible to isolate and classify each type of fault in the pitch system in wind turbines.